Exceedingly biocompatible and thin-layered reduced graphene oxide nanosheets and its application in co-delivery of curcumin and paclitaxel shows highly potent synergistic anticancer effects in A549 and MDA-MB-231 cells - Muthoosamy, Kasturi (2016)
Delivery of anti-cancer drugs using graphene and its derivatives: graphene oxide (GO) and reduced graphene oxide (RGO) has sparked major interest in this emerging field. The anti-cancer therapies often pose a limitation of insolubility, administration problems and cell-penetration ability. In addition, systemic toxicity caused by lack of selective targeting towards cancer cells and inefficient distribution limits its clinical applications. Graphene nanocomposite is a promising tool to address these drawbacks. Graphene is a flat monolayer of carbon atoms that holds many promising properties such as unparalleled thermal conductivity, remarkable electronic properties, and most intriguingly high planar surface and superlative mechanical strength, which are attractive in biotechnology applications.